Meetings, images and crossings in the album Clube da Esquina (1972) - Julião, Rafael Barbosa (Revista Criação & Crítica, 2020)
Between the 1960s and 1970s, Milton Nascimento's meeting with composers from Belo Horizonte started a circuit of collective creation, with fertile consequences for the history of popular songs in Brazil. The movement became known as Clube da Esquina, as well as the album that made it famous. The purpose of this article is to analyze the album Clube da Esquina (1972), as an integral aesthetic object, product of a collective elaboration, proceeding to the appreciation of songs, with special attention to the lyrics, but also to the narrative they form when taken together.